2004
DOI: 10.1002/jca.10080
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy using autologous monocyte‐derived dendritic cells pulsed with leukemic cell lysates for acute myeloid leukemia relapse after autologous peripheral blood stem cell transplantation

Abstract: Although a second stem cell transplantation (SCT) can be used as salvage therapy in patients with relapsing leukemia after SCT, most of these patients have a poor outcome. We tried clinical vaccination using monocyte-derived dendritic cells (DCs) pulsed with leukemic lysates to treat relapsing acute myeloid leukemia (AML) after autologous SCT. To generate DCs, CD14+ cells isolated from peripheral blood stem cell products were cultured in AIM-V in the presence of GM-CSF and IL-4. Adding TNF-alpha on day 6 induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 14 publications
1
44
0
1
Order By: Relevance
“…In contrast to peptide-vaccination studies, which have shown clinical activity in AML (9-13), DC vaccination in AML patients to date has been ineffective or inconclusive (51)(52)(53). The clinical effectiveness of our DC approach may be caused by several factors.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In contrast to peptide-vaccination studies, which have shown clinical activity in AML (9-13), DC vaccination in AML patients to date has been ineffective or inconclusive (51)(52)(53). The clinical effectiveness of our DC approach may be caused by several factors.…”
Section: Discussionmentioning
confidence: 88%
“…Second, we were able to obtain DC from blood CD14 + monocytes in all cases from AML patients in remission, in contrast to the generation of DC from primary AML cells, which was only successful in a minority of patients tested (53). Third, the choice of the WT1 antigen (33), rather than leukemic cell lysates or AML-derived DC (51)(52)(53), may also be advantageous, because WT1 is already recognized immunologically in AML patients (8,55,56); furthermore, WT1-targeted vaccine approaches have been successful in increasing the specific immune response in such a way that they can control AML, at least in some patients, as evidenced here and in other studies (10)(11)(12). Fourth, our unique clinical trial design (57), which is in stark contrast to current DC trials focusing on end-stage cancer patients, may have contributed to the demonstrable clinical effects observed (58).…”
Section: Discussionmentioning
confidence: 99%
“…A similar increase of proliferating T cells during DC vaccinations has also been reported for patients with prostate cancer, solid tumors and acute myeloid leukemia. [42][43][44] Fluorescence-activated cell sorting analysis of PB lymphocyte populations before and during immunotherapy demonstrated that the percentage of CD3 þ cells as well as CD4 þ and CD8 þ T lymphocytes was significantly higher in patients with clinical response and stable disease comparing to the patients, who did not respond to the therapy. These observations seem to confirm the hypothesis of Wierda et al, 45 suggesting the key role of the immunocompetence of the patients for positive results of immunotherapy in B-CLL patients.…”
Section: Vaccination Of B-cll Patients With Autologous Dendritic Cellmentioning
confidence: 99%
“…Large-scale production of AMLDCs in cell factories under GMP conditions yielded an adequate quantity of viable and mature AML-DCs (99). In another study, monocyte-derived DCs induced a peptide-specific cellular response (100 Leukemic-specific T cell responses were detected in some patients with AML with administration of AML lysate-pulsed monocyte-derived DCs (102,103). Immunotherapy is thought to be most effective at eradicating MRD, which is not done by immune cells themselves because they have been compromised by high-dose chemotherapy or radiation therapy (104,105).…”
Section: Leukemia-derived Dcs For Clinical Use and Results Of Clinicamentioning
confidence: 99%